A Sequence Is Defined Recursively By The Formula F(n+1)=f(n)+3

5 min read Aug 29, 2024
A Sequence Is Defined Recursively By The Formula F(n+1)=f(n)+3

A Recursive Sequence: f(n+1) = f(n) + 3

This article will explore a recursive sequence defined by the formula f(n+1) = f(n) + 3. We will delve into understanding what this formula means, how to find terms in the sequence, and the overall behavior of this type of sequence.

Understanding the Formula

The formula f(n+1) = f(n) + 3 defines a recursive sequence. This means that each term in the sequence is defined in terms of the previous term. Let's break down the formula:

  • f(n+1): This represents the next term in the sequence.
  • f(n): This represents the current term in the sequence.
  • + 3: This indicates that to find the next term, we add 3 to the current term.

In simpler words, this formula tells us that to get the next number in the sequence, we simply add 3 to the current number.

Finding Terms in the Sequence

To find terms in the sequence, we need an initial value or a starting point. Let's assume our initial value is f(1) = 2.

Here's how we can find the first few terms:

  • f(1) = 2 (Our initial value)
  • f(2) = f(1) + 3 = 2 + 3 = 5
  • f(3) = f(2) + 3 = 5 + 3 = 8
  • f(4) = f(3) + 3 = 8 + 3 = 11

Continuing this process, we get the sequence: 2, 5, 8, 11, 14, 17...

Behavior of the Sequence

This sequence is an arithmetic sequence. This means that the difference between any two consecutive terms is constant. In our case, the constant difference is 3.

The behavior of an arithmetic sequence is predictable. The terms will always increase (or decrease if the constant difference is negative) at a constant rate.

General Formula

We can also find a general formula for this sequence that doesn't rely on recursion. Since the sequence is arithmetic, we can express it as:

f(n) = f(1) + (n - 1) * d

where:

  • f(n): The nth term of the sequence
  • f(1): The first term of the sequence
  • n: The position of the term in the sequence
  • d: The common difference (in our case, d = 3)

Therefore, the general formula for our sequence is:

f(n) = 2 + (n - 1) * 3

This formula allows us to directly calculate any term in the sequence without needing to calculate the previous terms.

Conclusion

The recursive formula f(n+1) = f(n) + 3 defines an arithmetic sequence with a constant difference of 3. We explored how to find terms in the sequence and established the predictable behavior of arithmetic sequences. Understanding recursive sequences is crucial in various areas of mathematics and computer science, especially when dealing with iterative processes and algorithms.